The effect of inclined periodic magnetic field on natural convection flow of Al2O3-Cu/water nanofluid inside right isosceles triangular closed spaces - Geridonmez, B. Pekmen; Öztop, Hakan Fehmi (Elsevier Sci Ltd, 2022)
In this study, the effect of inclined partial periodic magnetic field on natural convection flow of a hybrid nanofluid in isosceles right triangular cavities is numerically investigated. The presence of periodic partial magnetic field is also compared with the full magnetic field. Steady, dimensionless governing equations in stream function-vorticity formulation are approximated by radial basis function based partition of unity method. Further, periodic magnetic field is kept at a fixed inclination angle regarding to the symmetry axis of its sinusoidal wave structure. The considered main parameters are Hartmann number (0 <= Ha <= 100) and period of the periodic magnetic field (0.25 <= A <= 1). The augmentation in Lorentz force is resulted with decrease in fluid velocity and convective heat transfer. Inhibitive effect at period one of periodic magnetic field is significantly noticed at all considered cases. Partial periodic magnetic field may be a good controller wherever fluid motion and temperature are to be stabilized inside the cavity.
Keywords: Triangular cavity; Partial magnetic field; Periodic magnetic field; Radial basis functions; Al2O3-Cu/water hybrid nanofluid